The Effect of Good Corporate Governance (GCG), Green Accounting, And Environmental Performance on Corporate Social Responsibility (CSR) (Study of Manufacturing Companies Listed on the IDX in 2021-2023) - Nadhifah, Nafisatun; Kartika, Indri (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to obtain empirical evidence on the influence of good corporate governance (GCG), green accounting, and environmental performance on corporate social responsibility (CSR) disclosure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A total of 139 companies were selected using a purposive sampling technique and analyzed through multiple linear regression. The results reveal that good corporate governance and environmental performance each exert a significant positive influence on CSR disclosure, reinforcing the role of internal control and sustainability practices in promoting transparency. In contrast, green accounting was found to have no significant effect. This non-significant result may stem from variations in the adoption and maturity of green accounting practices across firms, or potential inconsistencies in how green accounting is defined and measured within the Indonesian context. Therefore, future research should consider refining the operationalization of green accounting to capture its potential impact more effectively. Overall, the findings underscore the importance of robust governance and environmental strategies in improving CSR disclosure quality and provide meaningful insights for both corporate management and stakeholders.